2019
DOI: 10.1177/1557988319873532
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Masculine Norms and Mental Health on Health Literacy Among Men: Evidence From the Ten to Men Study

Abstract: Background: Adherence to masculine norms, such as self-reliance, has been thought to predict lower health literacy. Additionally, males with poor mental health may have low health literacy. Using two waves of the Ten to Men cohort, the current study examined whether masculinity and depressive symptomology explained three aspects of health literacy among men. Methods: Three subscales of the Health Literacy Questionnaire were used as the outcomes: Ability to find good health information; Ability to actively enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 35 publications
1
42
0
5
Order By: Relevance
“…This means that for this particular age group and culture, the gender expectation to deal on their own with all problems carries the highest risks to general well-being. This 'cluster' of correlations is in line with some previous studies that have shown poorer mental well-being among men who are highly self-reliant (Milner, et al, 2018, Milner, Shields & King, 2019Rice, Fallon & Bambling, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…This means that for this particular age group and culture, the gender expectation to deal on their own with all problems carries the highest risks to general well-being. This 'cluster' of correlations is in line with some previous studies that have shown poorer mental well-being among men who are highly self-reliant (Milner, et al, 2018, Milner, Shields & King, 2019Rice, Fallon & Bambling, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Although these professionals are more exposed to the disease than most of the population, factors that can help us understand this decline are greater access of these professionals to health services and broader knowledge about COVID-19 prevention and treatment. The literature has indicated that health literacy, that is, greater knowledge about diseases, their risk factors, self-care and trained health professionals and services for treatment, contribute to better mental health rates 32,33 . However, in any case, it is worth emphasizing that health professionals were mostly under social distancing measures, which could decrease the likelihood to be infected, and, therefore, alleviate anxiety related to the disease and the risk of mental disorder.…”
Section: Discussionmentioning
confidence: 99%
“…It is also essential to develop interventions in primary care focused on prevention, such as health literacy campaigns and actions 32,33 . In this sense, it is understood that easily understood information related to prevention, contagion, and mental health care becomes essential for the population.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Recent studies reveal that numerous social determinants of health exert strong influence on health literacy. Culture, gender and age have been identified as particularly powerful variables (Baum, 2019; Beauchamp et al, 2011; Bröder et al, 2017; Crengle et al, 2018; Lie et al, 2014; Milner et al, 2019; Peerson & Saunders, 2011). The nexus between these determinants, and their collective relationship with health literacy, remains largely unexplored.…”
mentioning
confidence: 99%